2021
DOI: 10.1016/j.ultrasmedbio.2021.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Use of Microbubbles and Ultrasound in Acute Peripheral Arterial Thrombosis: A Systematic Review

Abstract: Catheter-directed thrombolysis (CDT) for acute peripheral arterial occlusion is time consuming and carries a risk of major hemorrhage. Contrast-enhanced sonothrombolysis (CEST) might enhance outcomes compared with standard CDT. In the study described here, we systematically reviewed all in vivo studies on contrastenhanced sonothrombolysis in a setting of arterial thrombosis. A systematic search of the PubMed, Embase, Cochrane Library and Web of Science databases was conducted. Two reviewers independently perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…In the field of biomedicine, ultrasound-accelerated thrombolysis has recently emerged as a promising technique for treating thrombosis by transmitting sound waves to blood clots [ 48 50 ]. Currently, common ultrasound thrombolysis equipment is based on focusing the ultrasound transducer structure, which requires accurate focus control during the treatment process.…”
Section: Resultsmentioning
confidence: 99%
“…In the field of biomedicine, ultrasound-accelerated thrombolysis has recently emerged as a promising technique for treating thrombosis by transmitting sound waves to blood clots [ 48 50 ]. Currently, common ultrasound thrombolysis equipment is based on focusing the ultrasound transducer structure, which requires accurate focus control during the treatment process.…”
Section: Resultsmentioning
confidence: 99%
“…A recent analysis [ 91 ] of studies using MBs and ultrasound in peripheral arterial thrombosis reviewed eight clinical stroke studies, including two case series [ 92 , 93 ]. There was high heterogeneity among the studies, which made it impossible to perform a meta-analysis.…”
Section: Randomized Controlled Trialsmentioning
confidence: 99%
“…Its mechanisms include thrombus fragmentation and augmented penetration of thrombolytic agents [ 112 ]. A systematic review included 35 studies and found that the recanalization rates in the group that conducted sonothrombolysis were higher, suggesting that combined microbubbles and ultrasound is a safe and effective strategy for thrombosis treatment [ 113 ].…”
Section: Biomedical Applicationsmentioning
confidence: 99%